Effects of Game Characteristics and Player Positions on Concussion Incidence and Severity in Professional Football. Issue 12 (18th December 2018) - Dai, Jennifer B.; Li, Adam Y.; Haider, Syed F.; Tomaselli, Raechel; Gometz, Alex; Sobotka, Stanislaw; Post, Alexander F.; Adams, Ryan; Maniya, Akbar Y.; Lau, George K.; Kaye-Kauderer, Halley P.; Lovell, Mark R.; et al.
Background: Increasing efforts have been made to reduce the incidence and severity of concussion in high-contact sports. Despite these efforts, a relative lack of knowledge is available regarding modulating factors affecting concussion injury. Purpose: To analyze the potential influence of game characteristics and outcomes on concussion incidence and severity in professional football. Study Design: Descriptive epidemiology study. Methods: PBS Frontline Concussion Watch was used to collect concussion injury data from regular-season games of 32 National Football League (NFL) teams from 2012 to 2015. Game characteristic variables such as rushing and passing attempts, turnovers, and margin of victory were collected from ESPN. Analysis included descriptive statistics, analysis of variance, t tests, and correlation tests. Results: Away teams demonstrated a significantly greater concussion incidence per game than home teams. Losing teams had a significantly greater concussion incidence per game than winning teams. Being both the away team and the losing team appeared to have an additive effect. The home-versus-away and win-versus-loss effects were significant for offensive but not defensive positions. Within individual positions, significantly greater concussion incidence was associated with tight ends, running backs, wide receivers, and cornerbacks. When running versus passing positions were compared, passing positions (wide receiver, tight end, cornerback, safety) had significantly greater concussion incidence. A total of 626 games were missed as a result of reported concussions. Away teams had significantly more games missed due to concussion when they lost. Play time did not significantly differ before or after concussion injury. Other game characteristic variables did not significantly affect concussion frequency or intensity. Conclusion: Position, game location, and game outcome affect concussion incidence for professional football players. In a subset of analyses, the number of games missed aligned with concussion incidence, but this appeared to be an imperfect measure. These findings highlight new factors that may modulate concussion incidence and merit further study on how they may influence concussion evaluation.